Estresse em professores de educação física: potenciais causas e estratégias de enfrentamento - Diagnes Morostica; Adelar Aparecido Sampaio (Universidade Estadual do Oeste do Paraná, 2015)
The study deals with stressful situations in the context of performance of physical education teachers, aiming to recognize the potential causes and strategies used. The methodology used was characterized as descriptive with qualitative approach and included the participation of five teachers of the State school system acting in an inland city of state of Paraná. As data collection instrument it was used demographic questionnaire and interview, treated with content analysis. The results were organized into three categories of analysis, whence mainly in Category 1, stress causes: the lack of interest and lack of discipline of students, professional devaluation, excessive number of students, difficulty in meeting the demands of content to students, and accumulation of tasks. Category 2, consequences of stressful situations: gastrointestinal problems; physical and mental fatigue; feeling of fear and insecurity for the violence to teachers in schools. Category 3, forward strategies to stressful situations: dialogue with students and teachers, decision-making with more reflection, spirituality of experience, identification and motivation to the profession. We suggest intervention programs to optimize the professional development of teachers, as well as socio-political measures, particularly in the context of Physical Education.